2010
DOI: 10.5194/nhess-10-73-2010
|View full text |Cite
|
Sign up to set email alerts
|

Deformation pattern of the 6 and 7 April 2009, <i>M</i><sub>W</sub>=6.3 and <i>M</i><sub>W</sub>=5.6 earthquakes in L'Aquila (Central Italy) revealed by ground and space based observations

Abstract: Abstract. The deformation pattern of the 6 and 7 April 2009 MW=6.3 and MW=5.6 earthquakes in L'Aquila is revealed by DInSAR analysis and compared with earthquake environmental effects. The DInSAR predicted fault surface ruptures coincide with localities where surface ruptures have been observed in the field, confirming that the ruptures observed near Paganica village are indeed primary. These ruptures are almost one order of magnitude lower than the ruptures that have been produced by other major surrounding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…We demonstrated the subsidence in the LOS ranges from 25.1 cm to 28.1 cm from two ALOS PALSAR and two ENVISAT ASAR interferograms, respectively. The outcome of our work, are fully consistent with that of Walters et al (2009), GEER (2009) and Papanikolaou et al (2010. These references are also in agreement with the results achieved by Goudarzi et al (2011), that the greatest gradients are on the north-east area of the ENVISAT ASAR interferograms.…”
Section: Introductionsupporting
confidence: 94%
“…We demonstrated the subsidence in the LOS ranges from 25.1 cm to 28.1 cm from two ALOS PALSAR and two ENVISAT ASAR interferograms, respectively. The outcome of our work, are fully consistent with that of Walters et al (2009), GEER (2009) and Papanikolaou et al (2010. These references are also in agreement with the results achieved by Goudarzi et al (2011), that the greatest gradients are on the north-east area of the ENVISAT ASAR interferograms.…”
Section: Introductionsupporting
confidence: 94%
“…During movement along a normal fault, which means a downthrow of the hanging wall block, we observe, also, significant coseismic uplift within the footwall of the fault during an earthquake. The recent L'Aquila earthquake (6th April 2009) demonstrated that the ratio of the footwall uplift versus the hanging wall subsidence is around 0.3 [37]. Therefore, ongoing faulting and the de- velopment of listric normal faults has led to a tilted block, which partly separated a stretch of water, in a lagoon-like setting, from the lake.…”
Section: Discussionmentioning
confidence: 99%
“…Since tectonic uplift is a minor amount of coseismic displacements, vertical differences on a metre-scale between two notches are not reasonable for single and successive normal faulting earthquake events. More common are uplifting values in the order of a few decimetres (Papanikolaou et al, 2010). Hence, a mesoscale downward widening of pre-existing tidal notches is likely.…”
Section: Discussion and Concluding Marksmentioning
confidence: 99%
“…Stewart and Vita-Finzi, 1996;Armijo et al, 1996;McNeill et al, 2005;Papanikolaou et al, 2010). Pirazzoli et al (1994) identified a series of four tidal notches of Holocene age at Heraion (Figure 1), each displaced by repeated uplifts of about 0.8 ± 0.3 m. Assuming a ratio of ¼ net slip per event, this would equate to 4 m total offset in an area where Jackson et al (1982) reported just a minor coseismic uplift of 0.2 m during the Alkyonides earthquake sequence (M = 6.4-6.7) in spring 1981.…”
Section: Introductionmentioning
confidence: 99%